THE ENFORCEMENT OF THE LAND REGULATORY FRAMEWORK AGAINST ABANDONED AND ABSENTEE LAND - Kholil, Muhammad; Hasmiati, Rahmatullah Ayu; Elviandri; Surahman (Awang Long Law Review, 2025)
This research is motivated by the increasing problem of abandoned land and absentee land, which indicates the ineffective enforcement of the land regulatory framework despite the comprehensive formulation of normative frameworks such as the Basic Agrarian Law (UUPA), Government Regulation No. 20 of 2021, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (BPN) No. 20 of 2021. Uncultivated land and agricultural land ownership by owners not domiciled in the area result in inefficient use of space, increase the risk of agrarian conflict, and reduce the social function of land, as seen in Jonggon Jaya Village. This research aims to analyze the effectiveness of land regulatory framework enforcement, identify legal and administrative factors that hinder the handling of abandoned land and absentee land, and formulate strategies and formulations for strengthening the legal framework that is more responsive to local agrarian dynamics. The method used was sociological juridical research, combining normative analysis of land regulations with empirical findings through interviews, field observations, and review of land administration documents. These were then analyzed using Lawrence M. Friedman's legal system theory (structure, substance, and legal culture). The research results indicated that weaknesses in law enforcement stem from weak institutional capacity, fragmentation of legal substance, the absence of objective parameters for determining abandoned land, and low community compliance with land management obligations. To address these issues, this study offered five innovative policy formulations: the formulation of the Integrated Land Utilization Index (IULT), the development of Conditional Management Rights, the implementation of an electronic domicile verification system (E-DOM), the establishment of a Local Land Activation Fund, and the implementation of digital, electronically proven administrative protocols. These findings emphasize that strengthening the land regulatory framework requires synergy between normative reform, modernization of the administrative system, and strengthening of the community's legal culture to achieve sustainable agrarian justice.